Developmental trauma: Conceptual framework, associated risks and comorbidities, and evaluation and treatment - Cruz, Daniel; Lichten, Matthew; Berg, Kevin; George, Preethi (Frontiers in Psychiatry, 2022)
Children exposed to adverse childhood experiences (ACEs) and pervasive interpersonal traumas may go on to develop PTSD and, in most cases, will further undergo a significant shift in their developmental trajectory. This paper examines contemporary research on Developmental Trauma (DT), which is inextricably linked to disruptions in social cognition, physiological and behavioral regulation, and parent-child attachments. Developmental trauma associated with early experiences of abuse or neglect leads to multi-faceted and longstanding consequences and underscores critical periods of development, complex stress-mediated adaptations, and multilevel, trans-theoretical influences in the diagnostic formulation and treatment of traumatized children, adolescents, and adults. Psychological and medical correlates of Developmental Trauma Disorder are considered, and directions for future research are discussed.